2006
DOI: 10.3168/jds.s0022-0302(06)72085-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additional Milk Replacer Feeding on Calf Health, Growth, and Selected Blood Metabolites in Calves

Abstract: The objective of the experiment was to evaluate effects of increased milk replacer feeding on growth, intake, feed efficiency, and health parameters in stressed calves. Holstein bull calves (n = 120; approximately 3 to 8 d of age) were purchased from sale barns and dairy farms and housed in fiberglass hutches. In addition, wood shavings contaminated with coronavirus were mixed with clean shavings and added to each hutch before the start of the experiment. Calves were fed either a fixed amount (454 g/d) of a 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
141
9
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(197 citation statements)
references
References 24 publications
37
141
9
10
Order By: Relevance
“…This also indicates that buffalo calves have the capability to tolerate higher levels of BUN without any harmful effects. An increase in BUN concentration with age has been reported in cattle calves by other investigators (Quigley, 1996;Quigley et al, 2006).…”
Section: Discussionmentioning
confidence: 67%
“…This also indicates that buffalo calves have the capability to tolerate higher levels of BUN without any harmful effects. An increase in BUN concentration with age has been reported in cattle calves by other investigators (Quigley, 1996;Quigley et al, 2006).…”
Section: Discussionmentioning
confidence: 67%
“…The introduction of concentrates into the diet early in calf life is important for the stimulation of reticulo-rumen development (Williams and Frost, 1992). Quigley et al (2006) reported an average daily intake of 0.5 kg of concentrates by 28 days of age in calves offered 454 g of MR/day and by 33 days of age in calves offered a variable amount -up to 908 g of MR/day. Based on these observations, it is likely that calves in the current study offered the lower MR feeding level commenced their intake of concentrate in significant quantities at an earlier age.…”
Section: Discussionmentioning
confidence: 99%
“…This could represent a direct effect of lactulose on gut morphology or an indirect effect of 3% lactulose inclusion on sweetness. Quigley et al (2006) reported that increasing the content of CP in MR increases ADG and efficiency of gain. Other trials in pigs observed no additional benefits from the use of lactulose (Krueger et al, 2002).…”
Section: Discussionmentioning
confidence: 99%